Ecoféminismes Radical - Bahaffou, Myriam (Feu! : abécédaire des féminismes présents, 2021)
Plutôt que de réduire le féminisme à des revendications faites à l’État, au patron, au chef ou à papa, pour plus de lois, plus de “sécurité”, à n’être que le porte-drapeau ou le cache-misère du capitalisme, de tel ou tel gouvernement nationaliste, ces histoires des féminismes présents rappellent et font résonner ensemble nos vies féministes. Ce livre fonctionne comme un abécédaire, un manuel, une boîte à outils, un dictionnaire amoureux, dans lequel échanger des idées, affûter des armes, écouter des voix, partager des expériences et des pratiques, vibrer pour des luttes présentes. Il s’adresse à tous·tes : il contient à la fois des ressources et foisonne de références utiles, de notions, mais il est fabriqué par des plumes et des voix, des points de vue situés sur des retours d’expériences collectives, des itinéraires politiques et intimes, des réflexions et des rétrospections sur des parcours, des engagements, des révoltes et des espoirs. En pluralisant les styles, en se situant à la fois du côté de la théorie et de la pratique, de la création, des écritures au “nous” et au “je”, il témoigne de la force d’une approche féministe de l’histoire intellectuelle et politique. Il est dédié à toutes les résistantes anonymes au quotidien des violences les plus crasses, à celles qui embrasent les tribunaux, cassent des genoux et brisent les vitrines, à celles qui inventent mille tactiques imperceptibles pour survivre et se mettre à l’abri, à la mémoire de celles dont les noms recouvrent les murs de nos villes la nuit, à la puissance des collectifs qui se font, à ceux qui se sont défaits, qui se sont (re)constitués ailleurs ou autrement, à ce qui nous lie.
Keywords: approches et analyses; cours; discours dominant; fem3100; féminisme décolonial; genre; identités LGBTQIA2+; inégalités; patriarcat; premier cycle; systèmes d'oppressions; thématiques; violences; écoféminisme

Portrait de la jeune fille en feu - Sciamma, Céline (The Criterion Collection, 2020)
France, 1760. Marianne est chargée de peindre le portrait de mariage d'Héloïse, une jeune femme qui vient de quitter le couvent. Parce qu'elle est une future mariée réticente, Marianne arrive sous couvert de compagnie, observant Héloïse le jour et la peignant secrètement à la lumière du feu la nuit. Au fur et à mesure que les deux femmes tournent l'une autour de l'autre, l'intimité et l'attirance grandissent au fur et à mesure qu'elles partagent les premiers instants de liberté d'Héloïse. Le portrait d'Héloïse devient rapidement un acte de collaboration et un témoignage de leur amour.
Keywords: 1700-1799; amour; approches et analyses; cours; discours dominant; europe; fem3200; france; genre; identités LGBTQIA2+; liberté; patriarcat; premier cycle; périodes historiques; regard féminin; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; émotions

La Minotaure - Maréchal, Maël (Triptyque, 2019)
La Minotaure est un roman dans lequel une narratrice particulièrement terrifiée par l'idée de vivre témoigne de son enfance à travers des notes pour comprendre la source de ses effrois. La plupart de ses courts textes sont adressées à Maude, une amie décédée. Ce (faux) dialogue lui permet de tisser des liens entre son enfance et son âge adulte, et entre sa vie et sa mort qui, croit-elle, la guette à cause de cette tentation d'exister. C'est le récit d'une parole qui ose s'affirmer, d'une personne qui décide enfin d'exister à travers un noeud de violence patriarcale, blanche, impérialiste, de genre et de classe sociale qui l'étouffe, la transperce et l'invisibilise. C'est surtout l'histoire d'un millier de miroirs qui brisent sous une terrible impulsion à vivre.
Keywords: LGBTQIA2+; amériques; approches et analyses; arts; canada; classisme; cours; discipline; genre; histoire et politique; identité; identités LGBTQIA2+; lit3220; patriarcat; premier cycle; queer; québec; racisme; roman; régions géographiques; systèmes d'oppressions; thématiques; violences; écriture des femmes*; études littéraires

Sexualité - Weeks, Jeffrey; Mendès-Leite, Rommel; Collomb-Boureau, Colette; Millet, Baudoin; Baudry, Samuel (Presses universitaires de Lyon, 2014)
Première traduction française d’un ouvrage de Jeffrey Weeks, ce « manifeste intellectuel » est d’ores et déjà un classique anglo-saxon depuis plus de vingt ans. Dès sa première édition, il s’est imposé comme une introduction de pointe aux débats sur les sexualités, le genre et l’intime. Jeffrey Weeks retrace l’histoire de la sexualité, pensée comme une construction sociale, façonnée et remodelée inlassablement par le contexte dans lequel elle existe et s’exprime : la sexualité n’est ni naturelle ni uniforme, mais culturelle et plurielle. Cette approche pionnière permet de couvrir un large champ d’investigation : les traditions religieuses, les politiques identitaires, la mondialisation, l’impact social du sida, l’influence de la génétique et de la psychanalyse, la lutte des sexes, les nouveaux modèles familiaux... Désormais, dans sa troisième édition (qui fait l’objet de cette traduction), cet essai majeur intègre de nouveaux concepts et enjeux, issus en particulier des mouvements LGBT et des débats sur le mariage homosexuel.
Section: 1 vol. (303 p.) : couv. ill. en coul. ; 18 cm.
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; systèmes d'oppressions; thématiques

Dude, you're a fag: masculinity and sexuality in high school : with a new preface - Pascoe, C. J. (University of California Press, 2012)
"High school and the difficult terrain of sexuality and gender identity are brilliantly explored in this smart, incisive ethnography. Based on eighteen months of fieldwork in a racially diverse working-class high school, Dude, You're a Fag sheds new light on masculinity both as a field of meaning and as a set of social practices. C.J. Pascoe's unorthodox approach analyzes masculinity as not only a gendered process but also a sexual one. She demonstrates how the 'specter of the fag' becomes a disciplinary mechanism for regulating heterosexual as well as homosexual boys and how the 'fag discourse' is as much tied to gender as it is to sexuality"–Provided by publisher.
Keywords: 2000 à aujourd'hui; 2000-2009; 2010-2019; LGBTQIA2+; adolescents*; amériques; approches et analyses; californie; cours; discipline; ethnographie; hétérosexisme; masculinité; patriarcat; premier cycle; périodes historiques; régions géographiques; sciences humaines; sexisme; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Intersex: a perilous difference - Holmes, Morgan (Susquehanna University Press, 2008)
As threatening evidence that sex is not the natural basis upon which oppositional gender roles are built, the intersexed are made to disappear into normative categories, thus aligning once again the rightful place of male and female as opposites.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; patriarcat; personnes intersexes; premier cycle; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; violences; violences médicales

Manifeste cyborg et autres essais : sciences, fictions, féminismes - Haraway, Donna Jeanne (Exils, 2007)
La fin du XXe siècle, notre époque, ce temps mythique, est arrivé et nous ne sommes que chimères, hybrides de machines et d'organismes théorisés puis fabriqués ; en bref, des cyborgs. Le cyborg est notre ontologie ; il définit notre politique. Le cyborg est une image condensée de l'imagination et de la réalité matérielle réunies, et cette union structure toute possibilité de transformation historique. Dans la tradition occidentale des sciences et de la politique, tradition de domination masculine, raciste et capitaliste, tradition de progrès, tradition de l'appropriation de la nature comme ressource pour les productions de la culture, tradition de la reproduction de soi par le regard des autres, la relation entre organisme et machine fut une guerre de frontières... " Ainsi parle Donna Haraway. Ses textes traduits en plus de 16 langues en font une autrice incontournable de la scène intellectuelle internationale, penseuse de la postmodernité et des technosciences. La plus grande partie de son oeuvre est encore inédite en français. Bienvenue dans le monde de Donna Haraway peuplé de cyborgs, hybrides, femalemen, oncomice, coyotes et autres monstres. Il s'y déjoue les dichotomies anciennes : féminin / masculin ; nature / culture ; vivant / artefact. Bienvenue dans le monde de Donna Haraway, ses fabulations sont les nôtres, nos pires craintes ou nos meilleures espérances ? A l'évidence, les cartes politiques pour l'invention de nouveaux espaces. Cette anthologie propose les textes essentiels de Donna Haraway : Cyborg Manifeste, Situated Knowledge, Teddy Bear Patriarchy, Ecce Homo, Modest Witness, Race.
Keywords: LGBTQIA2+; anthologie; approches et analyses; corps; cours; cyborg; discipline; discours dominant; fem1000; fem3600; féminisme cyborg; genre; har4600; identités LGBTQIA2+; ontologie; patriarcat; point de vue situé; premier cycle; sciences humaines; systèmes d'oppressions; thématiques

Intersex Initiative: From "Intersex" to "DSD" - Koyama, Emi (2006)
keynote speech presented at Translating Identity conference held at University of Vermont in February 2006.
Keywords: EDI; LGBTQIA2+; approches et analyses; capacitisme; cours; discipline; intersexuation; patriarcat; premier cycle; queer; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

Thinking straight: the power, the promise, and the paradox of heterosexuality - Ingraham, Chrys (Routledge, 2005)
This collection of original essays will unravel the current heterosexual scene in two parts: one on rights and privileges, the other on popular culture. Topics covered include weddings, proms, citizenship, marriage penalties, cartoons, mermaids and myth.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; hétéronormativité; hétérosexisme; hétérosexualité; mariage; patriarcat; premier cycle; régions géographiques; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Make Room for Daddy: Anxious Masculinity and Emergent Homophobias in Neopatriarchal Politics - Stein, Arlene (Gender and Society, 2005)
What are the sources of continuing antipathy toward homosexuality, and what might they tell us about changing forms of American masculinity? This article documents some emergent homophobias circulating among conservative activists in relation to campaigns against gay rights in the early 1990s and against gay marriage in 2004. As feminist critiques of traditional masculinity make their way into conservative rhetoric and as men struggle to define a role that maintains male authority without sounding overly authoritarian, new forms of homophobia have emerged that are compatible with conservatives' quest to be seen as compassionate protectors of the family.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; amériques; anthropologie; approches et analyses; cours; discipline; homophobie; hétérosexisme; masculinité; militance; patriarcat; premier cycle; périodes; périodes historiques; régions géographiques; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; états-unis

L'hermaphrodite et la bisexualité à l'épreuve du droit dans l'antiquité - Cantarella, Eva (Diogène, 2004)
Traduit de l’italien.
Keywords: LGBTQIA2+; androgynie; antiquité; approches et analyses; bisexualité; cours; discipline; discours dominant; europe; grèce; grèce antique; his4860; homosexualité; identités LGBTQIA2+; intersexuation; inégalités; moeurs sexuelles; mythologie; patriarcat; premier cycle; périodes historiques; rapports sociaux; rome antique; régions géographiques; sciences humaines; sexualité; systèmes d'oppressions; thématiques

Quand les femmes se heurtent à la mondialisation - ATTAC (Mille et une nuits, 2003)
S'il est un effet de la mondialisation peu souvent mis en avant et dénoncé, c'est bien la détérioration de la condition des femmes. Certes, l'oppression des femmes est antérieure au capitalisme. Cependant, au lieu de favoriser la réduction des écarts entre hommes et femmes, le néolibéralisme s'appuie grandement sur eux pour en tirer le meilleur profit économique : les firmes transnationales, toujours à la recherche de main-d'oeuvre féminine, peu chère et corvéable à merci. n'hésitent èas à délocaliser ... Dans les pays du Nord, les emplois les plus précaires, souvent ultra-flexibles et à temps partiels incmbent aux femmes. Ne prennent-elles pas aussi en charge, dans de nombreux pays, la subsistance des familles, les soins e l'éducation des enfants, en suppléant aux carences des services privatisés? La Banque mondiale ne s'y est pas trompée, qui leur prête une grande attention puisque les femmes constituent une "variable" qui aide à encaisser les ajustements structurels ... Il convient de sortir de cet engranage. Aujourd'hui, au nord comme au sud, la lutte des femmes s'inscrit au coeur du combat altermondialiste : elles constituent une force vive dans le réseau international de résistance à la marchandisation du monde.
Keywords: approches et analyses; cours; droits des femmes*; fem1000; genre; histoire et politique; identités LGBTQIA2+; international; militance; mondialisation; patriarcat; premier cycle; systèmes d'oppressions; thématiques

Les familles homosexuelles aux États-Unis : dissolution d'un mouvement social ou redéfinition de sa portée politique? - Marche, Guillaume (Revue française d'études américaines, 2003)
Families are a challenge to the lesbian and gay movement in the United States, since homosexuality is largely construed as antithetical to "the family". By creating a wide variety of alternative families gays and lesbians however articulate an identity claim which may not be framed exclusively either in terms of assimilationism, or of differentialism. For this reason these alternative families present American society with a transformative potential which is in a position to exert its influence beyond the bounds of the gay and lesbian community. Far from being a hindrance in terms of efficiency, the very fact that these families constitute a private locus of gay and lesbian experience furthermore contributes to the lesbian and gay movement's expressive dimension, which is of crucial strategic importance in contemporary American society.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; discours dominant; famille; familles homoparentales; his4443; homoparentalité; hétérosexisme; identités LGBTQIA2+; lesbianisme; mouvements de libération; mouvements lgbt; mouvements queer; mouvements sociaux; parentalité; patriarcat; philosophie politique; premier cycle; queer; régions géographiques; sciences humaines; sciences sociales; systèmes d'oppressions; thématiques; états-unis; études américaines

The Quest for Modern Manhood: Masculine Stereotypes, Peer Culture and the Social Significance of Homophobia - Plummer, David C. (Journal of Adolescence, 2001)
This paper explores the use of homophobic terms by boys and young men and the meanings they invoke when using them. Highly detailed interviews were conducted with young men from diverse backgrounds about their own experiences while growing up and their observations of schools, teachers, family and peers. Homophobia was found to be more than a simple prejudice against homosexuals. Homophobic terms like “poofter” and “faggot” have a rich developmental history and play a central role in adolescent male peer-group dynamics. Homophobic terms come into currency in primary school. When this happens, words like poofter and faggot rarely have sexual connotations. Nevertheless, far from being indiscriminate terms of abuse, these terms tap a complex array of meanings that are precisely mapped in peer cultures, and boys quickly learn to avoid homophobia and to use it decisively and with great impact against others. Significantly, this early, very powerful use of homophobic terms occurs prior to puberty, prior to adult sexual identity and prior to knowing much, if anything, about homosexuality. An effect of this sequence is that early homophobic experiences may well provide a key reference point for comprehending forthcoming adult sexual identity formation (gay or not) because powerful homophobic codes are learned first.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; approches et analyses; australie; cours; discipline; homophobie; hétérosexisme; masculinité; nouvelle-zélande; océanie; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; violences

Something to tell you: the road families travel when a child is gay - Herdt, Gilbert H.; Koff, Bruce (Columbia University Press, 2000)
Even now, at the end of the twentieth century, many still have difficulty standing up and saying, "I am the parent of a gay child." Something to Tell You recounts the stories of families whose lives have been touched by the discovery that a child is lesbian or gay—how it affects and influences people's perceptions of their children and even changes the self-image of parents themselves. Focusing on fifty average families—not people seen in clinics or therapy—the authors found a consistent pattern of change: first negative, then positive. Sometimes the news led parents and siblings to form stronger bonds with the child, with each other, and with other relatives and friends. In many cases, their child's partner and partner's family grew to assume an important role in their own lives. In some cases, parents and siblings discovered new meaning in their lives through speaking out or joining PFLAG (Parents, Families, and Friends of Lesbians and Gays) and becoming part of the struggle for lesbian and gay rights. The authors found that families committed to staying together are typically able to overcome the powerful obstacles imposed by society. Something to Tell You also shows the lasting and sometimes tragic consequences for families who falter in the process of integration. Unwilling to accept their child's sexuality, some parents sought to blame each other, and all too often their own relationships unraveled as a result. Others who failed to tell close friends sometimes lost those friends through keeping secrets. Parents who neglected to form bonds with their child's partner fostered climates of alienation that persisted for years. A richly diverse collection of family stories, Something to Tell You is a book that will help break down widespread prejudice and put an end to destructive cultural myths. It affirms families' highest aspirations toward active love for their gay children, showing the steps to take toward new levels of support, solidarity, and love.
Section: xxii, 156 p. ; 24 cm.
Keywords: LGBTQIA2+; amériques; approches et analyses; cours; discipline; famille; hétérosexisme; patriarcat; premier cycle; relations familiales; régions géographiques; sciences humaines; soc2014; sociologie; systèmes d'oppressions; thématiques; états-unis

Same sex, different cultures: exploring gay and lesbian lives - Herdt, Gilbert H. (Westview Press, 1997)
Because homoerotic relations can be found in so many cultures, Gilbert Herdt argues that we should think of these relations as part of the human condition. This new cross-cultural study of gays, lesbians, and bisexuals around the world, Same Sex, Different Cultures provides a unique perspective on maturing and living within societies, both historical and contemporary, that not only acknowledge but also incorporate same-gender desires and relations. Examining what it means to organize "sex" in a society that lacks a category for "sex", or to love someone of the same gender when society does not have a "homosexual" or "gay/lesbian" role, Herdt provides provocative new insights in our understanding of gay and lesbians lives. Accurate in both its scientific conceptions and wealth of cultural and historical material, examples range from the ancient Greeks and feudal China and Japan to the developing countries of Africa, India, Mexico, Brazil, and Thailand, from a New Guinea society to contemporary U.S. culture, including Native Americans. For all of these peoples, homoerotic relations emerge as part of culture and not separate from history or society. In many of these groups, loving or engaging in sexual relations is found to be the very basis of the local cultural theory of "human nature" and the mythological basis for the cosmos and the creation of society. The mistake of modern Western culture, Gilbert contends, is to continue the legalization of prejudice against lesbians and gays. In this light, the book addresses the issue of "universal" versus particular practices and reveals positive role models that embrace all aspects of human sexuality. Finally, it offers knowledge of the existence of persons who have loved and have been intimate sexually and romantically with the same gender in other lands through divergent cultural practices and social roles. The most important lesson to learn from this cross-cultural and historical study of homosexuality is that there is room for many at the table of humankind.
Keywords: LGBTQIA2+; approche interculturelle; approches et analyses; cours; discipline; discours dominant; histoire; histoire et politique; hétérosexisme; patriarcat; premier cycle; sciences humaines; soc2014; sociologie; système colonial; systèmes d'oppressions; thématiques

The Heterosexual Imaginary: Feminist Sociology and Theories of Gender - Ingraham, Chrys (Sociological Theory, 1994)
This essay argues that the material conditions of capitalist patriarchal societies are more integrally linked to institutionalized heterosexuality than they are to gender. Building on the critical strategies of early feminist sociology through the articulation of a materialist feminist theoretical framework, the author provides a critique of contemporary sex-gender theory. She argues that the heterosexual imaginary in feminist sociological theories of gender conceals the operation of heterosexuality in structuring gender and closes off any critical analysis of heterosexuality as an organizing institution.... every sociological concept and thesis, as well as the overall patterning of these concepts and theses, is potentially open for reconsideration... With the emergence of feminist sociological theory, the critical emphases in sociology are strengthened by an insistence that sociological work be critical and change-oriented... in an intensely reflexive way towards sociology itself (Lengermann and Niebrugge-Brantley 1990:318). We must produce a political transformation of the key concepts, that is of the concepts which are strategic for us (Wittig 1992:30).
Keywords: LGBTQIA2+; approches et analyses; capitalisme; cours; discipline; féminisme matérialiste; histoire et politique; hétérosexisme; hétérosexualité; patriarcat; premier cycle; sciences humaines; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques

L'homosexualité masculine et les discours sur le sexe en contexte montréalais de la fin du XIXe siècle à la Révolution tranquille - Hurteau, Pierre (Histoire sociale / Social History, 1993)
La croyance populaire ainsi qu'une certaine théologie accordent souvent au discours religieux sur l'homosexualité une permanence doctrinale qu'il n'a pas. Les mythes populaires ont longtemps attribué la stigmatisation sociale de l'homosexualité au récit de Sodome. La critique historique du rapport entre religion et homosexualité permet cependant de mettre en évidence le caractère construit de ce discours et ses rapports avec le juridique et le médical. Le présent article veut établir de quelle manière ces discours ont pu s'élaborer au Québec, et particulièrement dans la région montréalaise, entre la fin du XIXe siècle et la Révolution tranquille. L'approche historique suggère une nouvelle herméneutique qui met en lumière les véritables impulsions qui sous-tendent le discours religieux sur l'homosexualité. Popular belief and certain types of theology often ascribe a continuity of doctrine to the religious discourse on homosexuality which, in fact, this discourse does not have. Popular myths have long attributed the social stigma of homosexuality to the story of Sodom. Historical criticism of the relationship between religion and homosexuality will bring to the fore the social construction of the religious discourse and its historical connections with the secular discourses of law and medicine. The following article will try to demonstrate how these discourses developed in Quebec, and particularly in the Montreal region, from the end of the nineteenth century to the Quiet Revolution. The historical approach taken here puts forward a new interpretation that brings to the light the real motivations that underlie the religious discourse on homosexuality.
Keywords: 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; 1950-1959; 1960-1969; LGBTQIA2+; Québec (Province); amériques; approches et analyses; canada; cours; discipline; discours dominant; discours religieux; his4860; histoire; histoire et politique; homophobie; homosexualité; hétérosexisme; montréal; patriarcat; premier cycle; périodes historiques; québec; religion; régions géographiques; révolution tranquille; sciences humaines; sexualité; soc2014; sofia; systèmes d'oppressions; thématiques

Nothing mat(t)ers: A feminist critique of postmodernism - Brodribb, Somer (J. Lorimer, 1992)
Nothing Mat(t)ers est une critique féministe des théories de Foucault, Derrida et Lacan, entre autres. Somer Brodribb analyse les textes et les arguments que le poststructuralisme a désignés comme centraux, exposant ainsi la misogynie en leur cœur. Brodribb fournit une histoire des définitions du structuralisme, du poststructuralisme, de la déconstruction et du postmodernisme
Keywords: approches et analyses; cours; discours dominant; fem1000; genre; histoire et politique; identités LGBTQIA2+; inégalités; patriarcat; postmodernisme; premier cycle; ressource en ligne; systèmes d'oppressions; thématiques

Rethinking masculinity: philosophical explorations in light of feminism - May, Larry; Strikwerda, Robert A.; Hopkins, Patrick D. (Rowman & Littlefield, 1992)
Are men naturally aggressive? What makes a good father? How can men form intimate friendships? In the new edition of this popular anthology, seventeen philosophers explore these and other questions that relate to what it means to be a man, including questions about pornography and homosexuality. New essays look at masculinity and violence, research on differences between men's and women's brains, impotence, sexual ambiguity, and whether black men have a moral duty to marry black women.
Section: xx, 236 pages
Keywords: LGBTQIA2+; approches et analyses; cours; discipline; discours dominant; histoire et politique; masculinité; masculinités; patriarcat; philosophie; premier cycle; rapports sociaux de sexe; sciences humaines; soc2014; systèmes d'oppressions; thématiques

Antiféminisme - Kreatur #13 - Regarder l’émission complète | ARTE
Lorsqu’on parle des mouvements d'extrême droite, populistes, ultraconservateurs ou encore des mouvements religieux, leur programme antiféministe est à peine évoqué. Ces soi-disant groupes de défense des droits des hommes sont pourtant aujourd’hui ouvertement opposés aux militantes féministes. Quelle est leur influence et surtout comment les affronter ?
Keywords: LGBTQIA2+; antiféminisme; approches et analyses; capitalisme; communication; corps; cours; discipline; documentaire; droits des femmes*; identités LGBTQIA2+; identités de genre; intersectionnalité; journalisme; patriarcat; pol5185; premier cycle; queer; ressource en ligne; sexisme; système colonial; systèmes d'oppressions; thématiques